Employment of refugees: a Malaysian perspective - Eishan Jan, Mohammad Naqib; Ali Mohamed, Ashgar Ali; Ahmad, Muhamad Hassan (USA Passion Development Sdn Bhd, 2018)
It is an undeniable fact that, despite not being a Party to the 1951 Convention Relating to the Status of Refugees (1951 Convention), Malaysia is exemplary in assisting refugees while they are waiting for the repatriation to their own country or resettle in a third country. However, the refugees recognised and registered in Malaysia with the United Nations High Commission for Refugees (UNHCR) are not financially supported by any institution. Therefore, they have no choice but to engage in employments which are not legally permitted under the Malaysian law. This situation opens the door for numerous forms of exploitation. In fact, the existing refugees in the country can contribute as active work in the local workforce and thereby increasing the productivity and generate revenue for the government. It can also reduce the reliance of foreign workers in the local labour market. Nonetheless, the employment of refugees can be challenging to engage for the stakeholders if there is no efficient and proper legal framework to govern the human resources practices for this aspect as there is no legislation dealing with the employment of refugees in Malaysia. Accordingly, this paper aims at identifying some challenges of the employment of refugees in enhancing the Malaysian economic growth. It also explores whether developing a legal framework in order to allow and enforce the employment of refugees in Malaysia would be feasible. This study is primarily doctrinal and qualitative in nature. The paper significantly contribute to some of the key focus areas in the Eleventh Malaysia Plan (2016-2020) such as improving labour productivity in the local economy, generating revenue for the government and promote human rights.